SUKSESI SEKUNDER PADA LAHAN TAMBAK TERLANTAR DI KAWASAN HUTAN MANGROVE SEGARA ANAKAN CILACAP JAWA TENGAH - Nugroho Edi Kartijono (The East Java Biological Society, 2004)
The study of secondary succession was carried out on Segara Anakan mangrove forest, since the secondary succession has been the significant problem in the mangrove forest Segara Anakan as the impact of illegal cutting and the neglected fishpond activities. Side-by-side comparisons method and quadrat sampling method were employed in this study. There were 3 areas of abandoned fishpond with different levels of succession. The sample stands were determinated subyectievely and the quadrat sample were put at random. Ordination method was used to see the correlation between vegetation pattern using environment parameters observed. The result of this study indicated that the important value on the stratum of mangrove herb was succession process. The ordination pattern of mangrove was not related to environment factors. In general, some spesies: Avicennia alba, Acanthus ilicifolius, Paspalum sp., Fimbristylis alboviridis, Bulbostylis puberula had the important role in the process of secondary succession.